Additive manufacturing of dense components in beta‑titanium alloys with crystallographic texture from a mixture of pure metallic element powders. (5th July 2019) - Nagase, Takeshi; Hori, Takao; Todai, Mitsuharu; Sun, Shi-Hai; Nakano, Takayoshi
Abstract: The fabrication of dense components composed of Ti-based alloys, i.e., Ti-X (X = Cr, Nb, Mo, Ta) alloys, from a mixture of pure elemental powders was achieved using selective laser melting (SLM) process. The Ti-Cr alloys comprise β-Ti single-phase components without any non-molten particles and macroscopic defects. The crystallographic texture of these β-Ti-Cr alloys can be controlled effectively by optimizing the build parameters. The development of {001}〈100〉crystallographic orientation during the SLM process is discussed based on the solidification process focusing on the columnar cell growth in the melt pool. These results demonstrate the possibility of fabricating the Ti-based alloy components with well-developed crystallographic texture from the mixture of pure elemental powders using the process of SLM. Graphical abstract: Unlabelled Image Highlights: Selective laser melting using a mixture of pure element powders was investigated. Dense components in Ti-X (X = Cr, Nb, Mo, Ta) alloys were fabricated. Ti-Cr alloy specimens exhibit a single β-Ti phase without any non-molten powders. Ti-Cr alloy specimens show {001}<100> crystallographic texture. The crystallographic texture formation during selective laser melting was analyzed.